Catalytic Enantioselective Simultaneous Control of Axial Chirality and Central Chirality in Allenes1. Issue 5 (15th March 2018) - Dai, Jianxin; Duan, Xinyu; Zhou, Jing; Fu, Chunling; Ma, Shengming
Abstract: Chiral molecules, which may contain one or more different type(s) of stereocentres, such as central, axial, planar, and helical chiralities, etc ., are indispensable in chemistry, pharmaceutical industry, and life science. Despite many advances for the preparation of chiral molecules usually with a single type of chirality have been realized, simultaneous construction of different types of chiralities is still a significant challenge. Here, we wish to report a protocol for preparation of chiral allenes with both central and axial chiralities via a catalytic asymmetric allenylation of different biologically or synthetically useful fluorinated or non‐fluorinated nucleophiles with readily available racemic allenes by using a single chiral ligand. An echoing between the central chirality and axial chirality for the enantioselectivity was observed. This strategy provides a general and practical approach to functionalized optically active allenes bearing both central and axial chiralities with an excellent enantioselectivity under mild conditions. Abstract : A protocol for preparation of chiral allenes with both central and axial chiralities via a catalytic asymmetric allenylation of different biologically or synthetically useful fluorinated or non‐fluorinated nucleophiles with one pair of diastereomer of racemic allenylic acetates by using a single chiral ligand was developed.